Scintigraphy of the Equine Pelvis - Chuthatep, Suwicha (2011)
Equine skeletal scintigraphy can be used in the diagnosis of pelvic injuries but thick overlying soft tissue is a factor that may decrease the detectability of lesions in this area. The purposes of this study were to examine the effects of soft tissue attenuation on the detectability of lesions and to evaluate the improvement of detectability by using computerized post processing of images. In this study, an equine pelvic phantom was produced using data from clinically normal horses to simulate the true appearance in a controlled and standardized setup. In an observational study, 11 observers evaluated scintigrams to find out the maximum depth of overlying soft tissue at which a lesion could be distinguished. Scintigrams with varying lesion contrasts, count levels, filtered and unfiltered and in two different colour displays were produced to evaluate factors influencing the detectability. The result showed that lesions with 130 percent contrast and less were obscured by overlying tissue that was 9 cm or more thick. Increasing the count level from 300 kcounts to 500 kcounts did not improve the lesion detectability. A Metz digital filter increased detectability of the lesion with 120 percent contrast of 50 and 150 kcounts scintigrams. Colour displays did not influence lesion detectability. The combination of an equine pelvic phantom and an observational study can be used to evaluate factors influencing the detectability in scintigrams. The results in this study show that less intense increase radiopharmaceutical uptake may be difficult to detect due to attenuation of thick overlying soft tissue.